2008
DOI: 10.3200/jrlp.142.6.633-644
|View full text |Cite
|
Sign up to set email alerts
|

Shyness and Cognitions: An Examination of Turkish University Students

Abstract: The authors aimed to examine the relation between shyness and dysfunctional relationship beliefs and to extend findings of previous studies to understand the role of fear of negative evaluation and self-esteem in shyness. Participants were 415 Turkish undergraduate students at Middle East Technical University. The participants completed Turkish versions of the J. M. Cheek and A. H. Buss (1981) Shyness Scale, the Interpersonal Cognitive Distortions Scale (Z. Hamamci & S. Büyükoztürk, 2004) the Brief Fear of Neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 50 publications
4
32
0
Order By: Relevance
“…Although the negative associations between shyness and interpersonal relationships have been reported by several other authors (e.g., Bruch et al ., ; Koydemir & Demir, ), to our knowledge, the present study is the first to investigate the bidirectional associations between shyness and interpersonal relationships longitudinally. The results indicated that increased shyness negatively predicted later interpersonal relationships.…”
Section: Discussionmentioning
confidence: 72%
“…Although the negative associations between shyness and interpersonal relationships have been reported by several other authors (e.g., Bruch et al ., ; Koydemir & Demir, ), to our knowledge, the present study is the first to investigate the bidirectional associations between shyness and interpersonal relationships longitudinally. The results indicated that increased shyness negatively predicted later interpersonal relationships.…”
Section: Discussionmentioning
confidence: 72%
“…V. Clark and Arkowitz 1975;Maddux and Stanley 1986). Further, shyer students tend to experience higher levels of social anxiety, social inhibition, and fear of judgment leading them to harbor greater fears of negative evaluation and interpersonal rejection (Koydemir and Demir 2008). It is perhaps not surprising then that shyness has been associated with lower academic performance (Dominguez et al 2010;Fantuzzo et al 2007).…”
Section: The Impact Of Student Characteristicsmentioning
confidence: 95%
“…In the related literature, there has been no research examining the relationship between cognitive distortions and self-handicapping. However, there have been several studies examining the relationship between self-esteem and cognitive distortions (e.g., Daly & Burton, 1983;Hamarta & Demirbaş, 2009;Koydemir & Demir, 2008;Mclennan, 1987;Nasir et al, 2011;Nielsen et al, 1996). The studies mention that when self-esteem is high, cognitive distortion is low, and vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…An individual with these thoughts makes humiliating definitions about themselves and their self-esteem; they perceive themselves as incomplete, worthless, or problematic (Hiçdurmaz & Öz, 2011). In related literature, it has been mentioned that the more cognitive distortions are used, the lower selfesteem becomes (Daly & Burton, 1983;Hamarta & Demirbaş, 2009;Koydemir & Demir, 2008;Mclennan, 1987;Nasir et al, 2011;Nielsen et al, 1996). According to Briere (2000), there are five types of cognitive distortions: self-criticism (low self-esteem), self-blame (a tendency for blaming oneself about negative events that are beyond one's control), helplessness (a general sense of helplessness concerning unwanted events in one's life), hopelessness (a belief that one's future is inescapably hopeless), and preoccupation with danger (an overestimation of the amount of danger and adversity in the world).…”
mentioning
confidence: 99%